Endoscope-Assisted Neuroportal Transcerebellar Approach to the Fourth Ventricle: An Anatomical Study - Piloni, Martina; Gagliardi, Filippo; Bailo, Michele; Barzaghi, Lina R.; Caputy, Anthony J.; Mortini, Pietro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Minimally invasive approaches to deep-seated lesions still represent a fundamental issue in modern neurosurgery. Tubular retractors allow to enhance the operability of intraventricular lesions, minimizing the risk of damages to brain parenchyma. Increasing interest for portal devices has been mainly focused on supratentorial pathologies, while transportal approaches in the posterior cranial fossa have been rarely described. In the present study, the authors aimed to investigate the surgical exposure and operability obtained with a microsurgical neuroportal transcerebellar approach targeting the fourth ventricle, assisted by endoscopic exploration.Material and Methods Six cadaveric specimens were provided for anatomical microsurgical dissection and Vycor ViewSite Brain Access System was used as tubular retractor. Surgical feasibility of the neuroportal transcerebellar approach was demonstrated through a definable and measurable parameter, the operability score.Results The neuroport provided a surgical corridor away from eloquent structures to target the whole fourth ventricle cavity, preventing injury to cerebellar nuclei and white matter pathways and, potentially, minimizing the risk of surgical morbidity. Maximal operability was reached in the pontomedullary junction and medullary area of the ventricular floor. Transportal endoscopic assistance contributed to a further extension of surgical exposure in blind spots, corresponding to the ipsilateral lateral recess, the uppermost part of the fourth ventricle, and the obex.Conclusion The neuroportal transcerebellar approach represents a viable alternative route to the fourth ventricle, avoiding vermian splitting or subarachnoid dissection of the cerebellomedullary cistern. Endoscopic assistance enhances the exposure of the surgical field and accomplishes a valid instrument for intraventricular orientation to ease microsurgical procedures.
Keywords: Cerebellum; dentate nucleus; fourth ventricle; neuroport; tubular retractor